Is the SES and academic achievement relationship mediated by cognitive ability? Evidence from PISA 2018 using data from 77 countries - Boman, Björn (Frontiers in Psychology, 2023)
Earlier research has suggested that that the international large-scale assessment, PISA (Programme for International Student Assessment), may be looked upon as a form of school test that is mostly explained by participating students’ socioeconomic status, non-cognitive factors, and various school factors, whereas another strand of research focuses on the similarities between PISA and cognitive ability assessments such as IQ tests. The latter position does also highlight the strong relationships between PISA scores and IQ test scores, typically aggregated to the country level. The current article adds to this scholarly debate by examining the latest PISA survey from 2018. The results of correlation, regression, moderator, and mediation analyses indicate that PISA scores indeed are strongly associated with both cognitive ability test scores and socioeconomic status indicators such as average annual national income. A more nuanced position suggests that PISA should be labelled a test that measures cognitive school skills, as the link between country-level abilities and school age abilities is neither causal, nor theoretically and empirically palpable, yet partly robust.